Modeling Absorbed Energy in Microwave Range for Nanocomposite Hot Melts Containing Metallic Additives - Radu F. Damian; Romeo Cristian Ciobanu (Applied Sciences)
This paper describes the simulation of the S (scattering)-parameters and absorbed energy for polymeric nanocomposites with metallic insertions (iron and aluminum, with two particle dimensions). The considered frequency domain, 0.1–3 GHz, is specific for a wide range of applications in microwave technologies. The actual limitations of electromagnetic simulations are described, along with an application related to the Nicolson–Ross–Weir procedure in infinite media, which opens new perspectives in nanocomposite electromagnetic modeling. It was demonstrated that, due to a higher conductivity, nanocomposites with Al particles can absorb a larger amount of energy compared to Fe particles within composite materials, at both insertion dimensions. At higher frequencies, the power loss density increases for both metals. The significant reduction in transmission, linked to a minimal reflection, verifies that for composites with added metallic powder, microwave energy is extensively absorbed by the materials, particularly at frequencies above 1.5 GHz, confirming their potential functionality as hot melts for advanced reversible bonding technologies.